School Culture Based on Islamic Values for Enhancing Teacher Performance in Primary Schools of Aceh Tamiang Regency - Wiwik Kalsum; Najmuddin Najmuddin; Hera Yanti (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study examines the impact of an Islamic value-based school culture on the improvement of teacher performance in elementary schools within Aceh Tamiang Regency, Indonesia. Although Islamic ideals have been incorporated into school traditions for an extended period, their assimilation into teachers' professional practices remains variable. This qualitative case study examines two public elementary schools—SD Negeri Alur Sentang and SD Negeri Paya Rahat—through in-depth interviews, non-participant observations, and document analysis. Utilizing Schein’s organizational culture theory and Bernardin & Russell’s performance model, the study investigates the expression of cultural artifacts, embraced values, and foundational assumptions that influence teacher conduct and work ethics. The findings indicate that Islamic cultural practices, including daily prayers, tadarus, and moral reminders, are evident yet not fully integrated into teachers' professional activity. The cultural dynamics are shaped by three main things: (1) artifacts that represent religious identity, (2) values that are important to people, such as discipline, amanah, and responsibility, and (3) beliefs that work is religion. All of these things together affect how well teachers do their jobs in terms of discipline, relationships with others, and devotion. Nonetheless, deficiencies persist in leadership modeling, implementation consistency, and community support. The study finds that to make Islamic value-based school culture stronger, we need strategic leadership, meaningful habituation, and working together. Suggestions are given to schools and policymakers to help teachers become more professional and culturally aware in a more complete way